2021
DOI: 10.1037/cbs0000280
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-related media consumption and parental mental health.

Abstract: Currently, little is known about the relationship between COVID-19-related media consumption and mental health among Canadian parents. Consequently, the current study aimed to investigate the associations between the consumption of COVID-19-related news and mental health in a large sample of Canadian families. We recruited 924 Canadian parents, between April 14th and August 9th 2020, to participate in an online survey, which assessed their demographics, media consumption patterns, and their levels of anxiety, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…As studies conducted with international samples have shown, the economic stresses of COVID-19 crisis have worsened parents' mental health and stress, especially for fathers in our sample, but also increased children's prosocial responses to the economic stress experienced by their parents (Francisco et al, 2020;Golding et al, 2021;Westrupp et al, 2021). But, as we show in this study, there are subtle but important differences in the ways mothers, fathers, and children's wellbeing have been affected by the pandemic.…”
Section: Discussionmentioning
confidence: 42%
“…As studies conducted with international samples have shown, the economic stresses of COVID-19 crisis have worsened parents' mental health and stress, especially for fathers in our sample, but also increased children's prosocial responses to the economic stress experienced by their parents (Francisco et al, 2020;Golding et al, 2021;Westrupp et al, 2021). But, as we show in this study, there are subtle but important differences in the ways mothers, fathers, and children's wellbeing have been affected by the pandemic.…”
Section: Discussionmentioning
confidence: 42%
“…The study found that the consumption structure has an impact on the self-rated health of the elderly to a certain extent. Specifically, clothing consumption, cultural consumption and other consumer goods reflecting social stratum differentiation have a significant impact on the self-rated health choices of the elderly [10]. In this study, clothing consumption and cultural consumption have a positive and significant impact on the elderly group which choose "general health".…”
Section: Discussionmentioning
confidence: 70%
“…Pursuing a healthy consumption lifestyle, including comprehensive consumption behaviors related to physical health, mental health and a healthy diet, is becoming more and more important for many people in Korea [9]. Golding and other Canadian scholars believe that, in the unprecedented period of COVID-19, the direct consumption of news media leads to depression and anxiety [10]. Bakkeli used Norwegian data to study consumption and housing ownership and proved that less consumption were significantly correlated with health, while housing property rights had no significant correlation with health [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, pandemic disruption seeped into family systems by way of altering co-parental cooperation and family cohesion (Browne et al, 2021 ; Peltz et al, 2021 ). Finally, in the pandemic-specific realm of disruption, caregivers reported heightened strain and commotion or chaos in their families (Cassinat et al, 2021 ), increased health-related anxiety (e.g., fears about the health of themselves or their loved ones or exposure to COVID-19; Peltz et al, 2021 ), challenges accessing usual healthcare and supplies/food, and overwhelm due to the consumption of news/media related to COVID-19 and digital emotion contagion (Golding et al, 2021 ; Offord Centre for Child Studies, 2020 ; Prikhidko et al, 2020 ).…”
Section: Pandemic-related Disruption In Families With Young Childrenmentioning
confidence: 99%